Supported ionic liquids for the removal of cyclophosphamide from aqueous solutions - Rocha, B. (2018)
The incidence of cancer is increasing and with it also the consumption of anti-cancer drugs. As with other drugs, these compounds are not completely metabolized and are excreted through the urine, ultimately reaching waste water treatment plants (WWTPs). Anti-cancer drugs are emerging pollutants, reinforcing the need for developing effective treatment or removal strategies. This work aims to contribute to the development of an efficient material for the removal of anti-cancer drugs, namely cyclophosphamide (CP), from urine. This strategy envisages the removal of anti-cancer drugs at the entrance point to avoid the contamination of water streams. To this end, six supported ionic liquids (SILs) were synthesized and characterized. A preliminary study was carried out to address the efficiency of these materials for the removal of CP from aqueous solutions. Kinetic and adsorption isotherms were determined for the best materials, and future studies will be carried out with urine samples.